Identitas Budaya dalam Novel Kembar Keempat Karya Sekar Ayu Asmara: Kajian Postmodernisme - Dewi Nur Fitriana (Universitas Islam Negeri Raden Mas Said Surakarta, 2017)
This article tries to examine cultural identity in novel Kembar Keempat written by Sekar Ayu Asmara by exposing postmodernism characteristic. This research uses descriptive-analysis method that is used to review postmodernism from Jean-Francois Lyotard. The result shows that in novel Kembar Keempat from Sekar Ayu Asmara, there is culture identity from postmodernism view of religion: as liberation and reformation, evasion of identity and masking: as shaping impression, and culture adaption: as a culture expression that borderless.Keywords:Postmodernism, Culture identity, Kembar keempat